The Effect of Silage and Different Protein Sources of Complete Feed of Ramie Waste on the Digestibility of Crude Fiber and Crude Fat Invitro Examination - Putri Awaliya Dughita; Adib Norma Respati (Journal of Livestock Science and Production, 2020)
The study aimed to examine the effect of silage and different protein sources of complete feed of ramie waste on the digestibility of crude fiber and crude fat. The study was conducted using 2x2 Factorial Complete Randomized Design (CRD) and Tukey (BNJ) further tests with complete feed of vegetable protein ramie waste without silage (CF0N), complete feed of vegetable protein silage (CF1N) ramie waste, CF1N complete feed, complete feed of animal protein ramie waste. silage (CF0H) and complete feed of animal protein silage ramie waste (CF1H) with 5 replications for each treatment. The parameters observed were crude fiber digestibility and crude fat digestibility. The material used is ramie waste, complete feed with vegetable protein supplementation (soybean meal and soybean groats), complete feed with supplementation of animal protein (fish meal) and then filtered for 14 days, after which an in vitro digestibility test was conducted according to the Tille and Terry method (1963) and crude fiber and crude fat test according to AOAC (2005). The data obtained were then analyzed using ANOVA and if the results were significant then proceed with the Tukey test (BNJ). The results showed that silage treatment and the addition of different protein sources on the digestibility of crude fiber had a very significant effect (P 0.01), and showed the interaction of crude fiber digestibility between silage and the addition of different protein sources namely CF0N 36.39%, CF0H 41, 63%, CF1N 40.20% and CF1H 42.80%. The results of the digestibility of crude fat showed no interaction of silage treatment and the addition of different protein sources, no significant effect (P 0.05). Keywords: Animal Protein, Complete Feed, Digestion, Ramie Waste, Vegetable Protein